Management of type 2 diabetes in pregnancy: a narrative review - Raets, Lore; Ingelbrecht, Anne; Benhalima, Katrien (Frontiers in Endocrinology, 2023)
The prevalence of type 2 diabetes (T2DM) at reproductive age is rising. Despite the shorter diabetes duration and lower HbA1c levels, wWomen with T2DM have a similarly high risk for pregnancy complications as pregnant women with type 1 diabetes. To reduce adverse pregnancy and neonatal outcomes, such as preeclampsia and preterm delivery, a multi-target approach is necessary. Tight glycaemic control together with appropriate gestational weight gain, lifestyle measures, and if necessary, antihypertensive treatment and low-dose aspirin is advised. This narrative review discusses the latest evidence on preconception care, management of diabetes-related complications, lifestyle counselling, recommendations on gestational weight gain, pharmacologic treatment and early postpartum management of T2DM.